Markov switching model of philippine stock market volatility - Almonares, Ray Anthony L. (Animo Repository, 2019)
A Markov-switching model was used to analyze the monthly return of the Philippine Stock Exchange, based on data from January 2000 to July 2017, to estimate the regime-switching behavior of the equity market. The study identified two states of the market: one characterized by positive mean return and low volatility, and another with negative mean return and high volatility. The high-volatility periods of the exchange were linked to various political and economic events. Results showed that the Philippine stock market reacted to domestic political issues that changed or challenged the country’s leadership. Economic events such as the Asian financial crisis, the country’s rapid currency depreciation, and the global financial crisis also prompted the local bourse to switch to a high-volatility state. © 2019 by De La Salle University.